Long‐term Caspian Sea level change. Issue 13 (12th July 2017) - Chen, J. L.; Pekker, T.; Wilson, C. R.; Tapley, B. D.; Kostianoy, A. G.; Cretaux, J.‐F.; Safarov, E. S.
Abstract: Caspian Sea level (CSL) has undergone substantial fluctuations during the past several hundred years. The causes over the entire historical period are uncertain, but we investigate here large changes seen in the past several decades. We use climate model‐predicted precipitation ( P ), evaporation ( E ), and observed river runoff ( R ) to reconstruct long‐term CSL changes for 1979–2015 and show that PER ( P ‐ E  +  R ) flux predictions agree very well with observed CSL changes. The observed rapid CSL increase (about 12.74 cm/yr) and significant drop (~−6.72 cm/yr) during the periods 1979–1995 and 1996–2015 are well accounted for by integrated PER flux predictions of ~+12.38 and ~−6.79 cm/yr, respectively. We show that increased evaporation rates over the Caspian Sea play a dominant role in reversing the increasing trend in CSL during the past 37 years. The current long‐term decline in CSL is expected to continue into the foreseeable future, under global warming scenarios. Key Points: PER flux‐reconstructed Caspian Sea level change agrees remarkably well with tide gauge and satellite measurements Increased evaporation rates over the Caspian Sea play a dominant role in reversing the Caspian Sea level trends during the past 37 years The current Caspian Sea level decline is expected to continue into the foreseeable future, under global warming scenarios